Industry clusters: an antidote for knowledge sharing and collaborative innovation?. Issue 1 (4th February 2014) - Connell, Julia; Kriz, Anton; Thorpe, Michael
Abstract : Purpose: – This paper seeks to focus on industry clusters and a rationale for why they may be considered an antidote for stimulating knowledge sharing and collaborative innovation. Design/methodology/approach: – Community based participatory research was undertaken using case studies and interviews within four industry clusters based in two countries – Australia and Dubai. Findings were ranked according to a knowledge sharing relational framework. Findings: – Industry clusters can play a key role in growing both established and new areas of economic development. Member firm collaboration, knowledge sharing and innovation can result in positive outcomes if the cluster is managed and facilitated appropriately and knowledge sharing is nurtured. Research limitations/implications: – The paper examines top-down, hybrid and bottom-up clustering from a variety of sectors as a way of understanding knowledge sharing and innovation exchange. However, given this research comprised case studies, it is recommended that broader, more internationally generalizable research is conducted that includes cluster firms within a range of sectors. Practical implications: – The stimulation of opportunities for collaboration and innovation are mandatory for firms and regions to move forward. Irrespective of the uncertainty of the outcome, cluster managers/facilitators need to ensure that they provide regular opportunities for cluster firms facilitators/managers and representatives to network and generate new ideas. Originality/value: – The role of cluster managers/facilitators in supporting knowledge sharing processes has been largely overlooked to date. Agglomeration needs both visible and invisible hands to stimulate knowledge sharing and exchange.